Analisis Tingkat Pemahaman Guru BK Terhadap Kode Etik Profesi Konselor dalam Mencegah Malpraktik - Zahraini, Novita; Nadhirah, Nadia Aulia; Budiman, Nandang (Universitas Sebelas Maret, 2023)
This research is aimed at analyzing the level of understanding of guidance and counseling teachers towards the code of ethics of the counselor profession and how they apply it in schools where they are assigned as guidance and counseling teachers. Understanding the professional code of ethics listed in ABKIN is very important for guidance and counseling teachers or school counselors to understand and apply with the aim of avoiding possible malpractice actions. The method used in this study is the SLR (system literature review) method which examines and discusses previous studies and draws conclusions from a discussion. The results of this literature review prove that the understanding of guidance and counseling teachers or school counselors on the code of ethics influences the provision of guidance and counseling services in schools. The higher the percentage of guidance and counseling teachers' understanding of the code of ethics, the better the implementation of guidance and counseling services and vice versa.